2012
DOI: 10.1038/emboj.2012.192
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human lung alveolar multipotent cells by a novel p38α MAPK/miR-17-92 axis

Abstract: Regulation of human lung alveolar multipotent cells by a novel p38α MAPK/miR-17-92 axisThis study characterizes putative human lung stem cells based on E-cadherin/Lgr6 expression. Long-term clonal expansion, the ability to form bronchioalveolar-like epithelia and the discovery of the miR-17-92 cluster as regulator of their proliferative capacity are features of this unique stem cell population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 43 publications
2
58
1
Order By: Relevance
“…The observed differences in the relative abundance of mature miRNAs from the miR-17~92 cluster by following treatment with miR-92a inhibitor can be attributed to several sources. While mature miRNAs can have half-lives of hours to days in vivo , it has also been demonstrated that mature miRNA species from miR-17~92 do not respond consistently to miR-17~92 depletion (4143) and that the secondary structure of the miR-17~92 primary transcript affects miRNA processing (44). The lack of response to the miR-92a inhibitor in mouse cells derived from murine KRASmt and KRASmt/p53null lung tumors suggests that the interaction between the miR-92a inhibitor and the miR-17~92 primary transcript may differ between the two organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in the relative abundance of mature miRNAs from the miR-17~92 cluster by following treatment with miR-92a inhibitor can be attributed to several sources. While mature miRNAs can have half-lives of hours to days in vivo , it has also been demonstrated that mature miRNA species from miR-17~92 do not respond consistently to miR-17~92 depletion (4143) and that the secondary structure of the miR-17~92 primary transcript affects miRNA processing (44). The lack of response to the miR-92a inhibitor in mouse cells derived from murine KRASmt and KRASmt/p53null lung tumors suggests that the interaction between the miR-92a inhibitor and the miR-17~92 primary transcript may differ between the two organisms.…”
Section: Discussionmentioning
confidence: 99%
“…E-Cad/ Lgr6 + single-cell injection in the kidney capsule produce differentiated bronchioalveolar tissue, while retaining self-renewal. 60 These cells may potentially act as endogenous lung stem cells. However, the use of both cells for lung recellularization has not been reported yet.…”
Section: Oeztuerk-winder and Colleagues Identified E-cad/lgr6mentioning
confidence: 99%
“…Shortly after description of c-kit+ human lung stem cells, the existence of another population of putative stem cells was reported[14]. These cells were characterized as positive for E-Cadherin and leucine-rich repeat-containing G-protein-coupled receptor 6 (E-Cad/Lgr6 + ) while being a sub-population of ITGA6 + cells.…”
Section: Lung Resident Stem/progenitor Cellsmentioning
confidence: 99%